Evaluation of the effectiveness of lip frenoplasty method on the amount of gingival coverage in paitent with gummy smile (clinical study) - يحيى هلا; حكمت يعقوب (Latakia University Journal -Medical Sciences Series, 2023)
-Research background and purpose: The gummy smile problem causes many patients to hide their smile when they are happy or when taking pictures. The gummy smile is defined as the excessive amount of upper jaw gum exposed while smiling. The problem of a gummy smile is a challenge for the dentist and surgeon to reach a satisfactory result aesthetically and functionally. Despite the multiplicity of ways to manage a gummy smile, whether using conservative or surgical methods, most of them need to repeat the procedure after a period of time. -The aim of the research is to evaluate the effectiveness of the lip frenoplasty in managing a gummy smile, thus reducing the amount of gingival exposure while smiling, and trying to maintain an aesthetically pleasing condition for as long as possible. Research materials and methods: The study was conducted on 15 patients with gummy smile problem The surgical treatment was performed according to the lip frenulum manufacturing technique, and the case was followed up for six months after the surgery, by taking optical images and analyzing them based on anthropometric analysis and using the paired samples test for a statistical study at the level of significance p<0.05. -Results : The results of the statistical analysis showed an improvement in the studied indicators during the observation period, as the study was able to maintain the improvement in the aesthetic aspect until the end of the observation period. -Conclusion: Within the limits of this study, gummy smile repair was effective and gave stable clinical results in the observation period in terms of the amount of gingival exposure when smiling.